3D printing-based cellular microelectrodes for high-performance asymmetric quasi-solid-state micro-pseudocapacitors. Issue 4 (3rd January 2020) - Wang, Teng; Tian, Xiaocong; Li, Liang; Lu, Luhua; Hou, Shuen; Cao, Guozhong; Jin, Hongyun
Abstract : A high-performance asymmetric quasi-solid-state micro-pseudocapacitor was fabricated using the 3D printing-enabled cellular graphene framework. Abstract : Micro-supercapacitor is a member of the miniaturized energy storage device family, which offers great advantages on power density and life span. However, the limited device capacitance and narrow voltage window limit its energy density, hindering its application. In the present work, a novel micro-pseudocapacitor (MPC) constructed via the facile extrusion-based 3D printing technique has been demonstrated to deliver efficient charge storage with high device capacitance and moderate voltage window. Such an asymmetric MPC is constructed with 3D-printing-enabled asymmetric interdigitated cellular microelectrodes; in which, one is Ni–Co–O nanosheets grown on macroporous 3D reduced GO (3DG) microelectrode and the other is MnO2 nanosheets grown on 3DG. Such an MPC offers facilitated fast electron transport, ionic diffusion, large number of active sites and desired porosity for electrolyte penetration. The asymmetric MPC shows a high specific capacity of 500 mC cm −2, an energy density of 90 μW h cm −2 and a voltage window of 1.3 V. A device cycling stability with 10 000 charge and discharge cycles is also achieved for the as-fabricated asymmetric MPCs. These encouraging results may open a new avenue to design and fabricate state-of-the-art miniaturized electrochemical energy storage devices with customized geometries.